2013
DOI: 10.1111/are.12212
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses and HSP70 mRNA expression of GIFT strain of Nile tilapia (Oreochromis niloticus) under cold stress

Abstract: An investigation on the physiological responses and HSP70 expression under cold stress was conducted on Genetically Improved Farmed Tilapia (GIFT) strain of Nile tilapia (Oreochromis niloticus). Tilapia were acclimated at 28°C as control and then the water temperature was reduced from 28°C to 15°C at a rate of 1°C h À1 , and serum biochemical indices, antioxidant enzymes and expression of HSP70 mRNA were analysed on days 0, 0.5, 1, 2, 3 and 5 after exposure to 15°C. The concentration of serum K, Na, Cl and Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 70 publications
2
19
0
Order By: Relevance
“…In the present study, SOD activity in the liver first decreased and then increased slightly with decreasing water temperature, whereas MDA content increased. The results of the current study were similar to previous studies on tilapia (Shi et al, ), swimming crab, Portunus trituberculatus (Meng, Liu, Li, Gao, & Chen, ), and puffer fish (Cheng et al, ). To date, many studies have confirmed that A. membranaceus and its extracts have significant antioxidant activities (Jia et al, ; X. L. Jiang et al, ; M. Li et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, SOD activity in the liver first decreased and then increased slightly with decreasing water temperature, whereas MDA content increased. The results of the current study were similar to previous studies on tilapia (Shi et al, ), swimming crab, Portunus trituberculatus (Meng, Liu, Li, Gao, & Chen, ), and puffer fish (Cheng et al, ). To date, many studies have confirmed that A. membranaceus and its extracts have significant antioxidant activities (Jia et al, ; X. L. Jiang et al, ; M. Li et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The HSP70/hsp70 expression in O. niloticus significantly increased at first under cold stress (Hassan, 2017;Shi et al, 2015) similar to the upregulation of flounder hsp70 expression in this study. Previous studies also demonstrated that HSP70 synthesis in fish was enhanced under low temperature (Shi et al, 2015;Weber & Bosworth, 2005).…”
Section: Differential Expression Of Hsp70 and Yb-1 Genes Under Coldsupporting
confidence: 85%
“…Under cold stress, physiological and histological responses of fish are the first to be considered, but the latter is rarely reported. In several fishes, such as Oreochromis niloticus and Albula vulpes , cold elevated prominently superoxide dismutase and catalase activities, and lactate concentration (Shi et al, ; Szekeres et al, ). These physiological responses need energy supplying.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations